Czechoslovak Socialist Civil Law in the Years 1948 – 1989 - Radovan Dávid (Journal on European History of Law)
This article deals with the Czechoslovak civil law in years 1948 - 1989. It is connected with the importance of the changes in the society in years 1948 and 1989 and describes their effects on the legal regulations as well as on the future development. The main aim of this article is to describe a relation between regulations adopted by constitution and regulations adopted in Civil Code as well as to analyze typical institutes of Czechoslovak civil law, for example personal use or structuralism of ownership.